The cellular structure of cork from Quercus cerris var. cerris bark in a materials’ perspective - Şen, Ali; Quilhó, Teresa; Pereira, Helena (Industrial Crops and Products, 2011)
Cork in the outer bark of trees is among the valuable raw materials of biological origin due to properties that result mainly from its cellular structure. Large scale commercial utilization of cork has been only achieved with cork from Quercus suber. Another oak species, Quercus cerris, also contains substantial, albeit not continuous, regions of cork that are clearly visible to the naked eye but are so far considered as a waste material. Bark samples of Q. cerris var. cerris trees were collected from the Andırın province, Turkey. Cork portions were separated and their cellular structure was investigated with optical and electron scanning microscopy observations. The results were compared with Q. suber cork. Q. cerris cork has the typical features of cork tissues with a regular and radially aligned structure of suberized cells without intercellular voids, showing a ring structure and a distinction of earlycork and latecork cells. Solid volume fraction was estimated at 25% (22% in earlycork, 36% in latecork). In Q. cerris cork cells are smaller, cell wall thickness and solid volume fraction are higher, and the tissue is less homogeneous with a higher content of ligniﬁed inclusions than in Q. suber cork. These factors will negatively inﬂuence quality in regard to density and mechanical properties associated to elasticity. However, this does not impair its use for production of granulates and agglomerates, e.g. for insulation and energy absorption. Separation of the cork fraction from the bark is a step required before further processing and use.
Keywords: Bark; Cellular structure; Cork; Quercus cerris; Quercus suber